Educational journey: from the Roman era, the Dutch colonial period, to Muhammadiyah in Indonesia - Fadhlurrahman, Fadhlurrahman (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2025)
Education in Indonesia has experienced a long journey, from the Dutch colonial period to the education development carried out by Muhammadiyah. This article aims to analyse the evolution of education in Indonesia by highlighting the influence of each period on the current education system. During the Dutch colonial period, education was used to strengthen colonial power, where access to education was very limited for indigenous peoples and prioritised colonial interests. However, this period also gave birth to awareness of the importance of education, which became the foundation for the Islamic education movement in Indonesia. The research method used in this article is the library research method, where data is collected from various literature sources, including books, journal articles, and other related documents. This approach allows researchers to analyse and interpret existing information comprehensively and provide a deeper context regarding the evolution of education in Indonesia over time. Muhammadiyah, which was founded in 1912, plays an important role in educational reform in Indonesia by integrating Islamic values in the curriculum and developing inclusive educational institutions. Through an approach that focuses on character and quality education, Muhammadiyah has established thousands of schools and universities that provide formal education and shape students' character according to Islamic values. Thus, Muhammadiyah's contribution to education reflects efforts to create a generation that is intelligent, noble, and ready to face global challenges. This article is expected to provide insight into the journey of education in Indonesia and the important role played by various historical periods in shaping the current education system.Pendidikan di Indonesia telah mengalami perjalanan panjang mulai dari masa penjajahan Belanda hingga perkembangan pendidikan yang dilakukan oleh Muhammadiyah. Artikel ini bertujuan untuk menganalisis evolusi pendidikan di Indonesia dengan menyoroti pengaruh setiap periode terhadap sistem pendidikan saat ini. Pada masa penjajahan Belanda, pendidikan digunakan sebagai alat untuk memperkuat kekuasaan kolonial, di mana akses pendidikan sangat terbatas bagi masyarakat adat dan mengutamakan kepentingan kolonial. Namun, periode ini juga melahirkan kesadaran akan pentingnya pendidikan, yang kemudian menjadi landasan bagi gerakan pendidikan Islam di Indonesia. Metode penelitian yang digunakan dalam artikel ini adalah metode penelitian perpustakaan, di mana data dikumpulkan dari berbagai sumber literatur, termasuk buku, artikel jurnal, dan dokumen terkait lainnya. Pendekatan ini memungkinkan peneliti untuk menganalisis dan menafsirkan informasi yang ada secara komprehensif, serta memberikan konteks yang lebih dalam mengenai evolusi pendidikan di Indonesia dari waktu ke waktu. Muhammadiyah yang didirikan pada tahun 1912 berperan penting dalam reformasi pendidikan di Indonesia dengan mengintegrasikan nilai-nilai Islam dalam kurikulum dan mengembangkan lembaga pendidikan yang inklusif. Melalui pendekatan yang berfokus pada karakter dan kualitas pendidikan, Muhammadiyah telah berhasil mendirikan ribuan sekolah dan universitas yang tidak hanya menyelenggarakan pendidikan formal, tetapi juga membentuk karakter siswa sesuai dengan nilai-nilai Islam. Dengan demikian, kontribusi Muhammadiyah terhadap pendidikan mencerminkan upaya menciptakan generasi yang cerdas, mulia, dan siap menghadapi tantangan global. Artikel ini diharapkan dapat memberikan wawasan tentang perjalanan pendidikan di Indonesia dan peran penting yang dimainkan oleh berbagai periode sejarah dalam membentuk sistem pendidikan saat ini.